2019
DOI: 10.1111/acer.14149
|View full text |Cite
|
Sign up to set email alerts
|

Increased Maternal Care Rescues Altered Reinstatement Responding Following Moderate Prenatal Alcohol Exposure

Abstract: Background: Fetal alcohol spectrum disorders (FASD) commonly include deficits in learning, memory, and executive control that can have a severe negative impact on quality of life across the life span. It is still unclear how prenatal alcohol exposure (PAE) affects executive control processes, such as control over reward seeking, that lead to inappropriate behavior later in life. Learning and reinstatement of a previously learned response after extinction is a simple, well-validated measure of both acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Studies using exposure models in mice and rats similar to those used in the current study further support this conclusion as studies utilizing the New Mexico Alcohol Research Center model have shown that this exposure generally spares learning processes including acquisition of instrumental responding, extinction of learned associations, visual discrimination and acquisition of spatial responses. In contrast, these exposures impair performance when task demands are increased either via reinstatement of reward after extinction or reversal of a learned visual or spatial discrimination 24,39,48 . Rat studies using this model that yield similar BAC (~80 mg/dL) also generally spare learning yet impair performance when contingencies are changed or reversed 49–51 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies using exposure models in mice and rats similar to those used in the current study further support this conclusion as studies utilizing the New Mexico Alcohol Research Center model have shown that this exposure generally spares learning processes including acquisition of instrumental responding, extinction of learned associations, visual discrimination and acquisition of spatial responses. In contrast, these exposures impair performance when task demands are increased either via reinstatement of reward after extinction or reversal of a learned visual or spatial discrimination 24,39,48 . Rat studies using this model that yield similar BAC (~80 mg/dL) also generally spare learning yet impair performance when contingencies are changed or reversed 49–51 .…”
Section: Discussionmentioning
confidence: 97%
“…Females continued to consume alcohol or saccharin solutions throughout the 5‐day mating period. Pregnancy was positively determined by monitoring weight gain every 3 to 4 days to minimize handling stress as previously described 23,24,37,39 . Access to alcohol was withdrawn beginning on postnatal day 0 using a step‐down procedure over a 6‐day period and offspring were weaned at approximately 23 days of age.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, other studies reported that maladaptive perseverative responses underlie inflexible behavior upon changes in contextual associations. In fact, in the absence of overt learning deficits, FAE adult mice display enhanced reinstatement of previously extinguished responses (108). These impairments are associated with reversal learning deficits, indicative of altered cognitive flexibility, in both adolescent and adult FAE offspring (43,102,(109)(110)(111).…”
Section: Executive Function Deficits Induced By Fetal Alcohol Exposurmentioning
confidence: 99%